(3OjhGf GdCHjhQOj (B((3GdfLOjGJ(B) (3GdbSe GdKGfjs - (3CHhGdeXaQ eMeO Hf CMeO Hf eMeO Hf eYGhjI GdCUZQ GdCehj GdCHjhQOj,J (B557 (3g` s
(3ChdgG (B:s
(3Ef CMb eG JUQa Edjg dge MeO ddg SHMGfg Ydi eG jJfGUQ ef fYe RgQI GdQjGV s
(3BNQgG (B:s
(3ef bUjOI dGejI(B: (3Rfj Gdbhe MJi JYQaj YfO hRfge EPG QaY GdejRGf cja Cejd s
(3Vef eLehY , JQJjHgG (B: (3ef U (B18 (3H (B- (3U(B69 (3Cs
(3GdfSNI HgG MhGTs
(3fSNI NGeSIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B209s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B18 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs